CYTOTOXIC EFFECTS OF PROTEIN FRACTION ISOLATED FROM Curcuma mangga VAL RHIZOMES AND CONTAINING RIBOSOME-INACTIVATING PROTEINS ON CANCER CELL-LINES AND NORMAL CELL - Sismindari Sismindari; Retno S. Sudibyo; Endang Astuti (Universitas Gadjah Mada, 2004)
C. mangga Val. has been used as an alternative remedy for cancer in Yogyakarta. The protein fraction of C. mangga was identified to contain Ribosome-inactivating Protein which cleave supercoiled double stranded DNA in vitro. In this experiment, the protein fraction isolated from fresh, 400C dried and freeze dried C. mangga Val. rhizome was screened against HeLa, Raji cell-lines and normal mononuklear cells for cytotoxic effects. This would enable us to describe the sensitivity of the protein extract on different cell types. The level of cytotoxicity was determined on the level of LC50 which was based on the percentage of the cell death following the 24 hours incubation with the extract.The protein isolated from C. mangga Val. was able to cleave supercoiled double stranded DNA to nick circular form. This result suggested that protein contained RIPs. The highest activity was identified in the protein isolated from fresh C. mangga Val, and this was followed respectively by freeze drying and 400C drying C. mangga Val. The comparison of the cytotoxic effect showed that protein of fresh C. mangga Val produced the largest number of death cells and the most toxic was on the HeLa cell line. Moreover, the LC50 indicated that the highest cytotoxic effect was shown by protein isolated from fresh C. mangga Val. followed respectively by freeze drying and 400C drying C. mangga Val. Based on LC50, the highest cytotoxic effect of C. mangga Val was found on HeLa cell line, while similar cytotoxic effect was appear on Raji cell line and normal mononuclear cells